مقومات الاستثمار الزراعي في مجال القمح في السودان خلال الفترة 1994-2022م - معتز ادم ،عبدالرحيم محمد; محمد حسن ،اسماعيل احمد; هويدا يس، محمد علي (جامعة الوادي University of Eloued, 2025)
هدفت الدراسة إلى التعرف على مقومات الاستثمار الزراعي في مجال إنتاج القمح في السودان مع الوصول إلى نتائج وتوصيات تسهم في الترويج للاستثمار في مجال إنتاج القمح وتسليط الضوء علي موقف الشراكات في مجال إنتاج القمح في السودان. افترضت الدراسة توفر مقومات الاستثمار الزراعي في مجال إنتاج القمح ولكنها لم يتم استغلالها الاستغلال الأمثل وعدم وجود شراكات إستراتيجية في مجال أنتاج القمح لمواجهة وتلبية الطلب المتزايد على القمح. اتبعت الدارسة المنهج الوصفي التحليلي الذي يعمل على وصف وتفسير الوضع القائم ومن ثم الوصول إلى نتائج وتوصيات تسهم في حل مشكلة الدراسة. خلصت الدراسة إلى نتيجة أن عدم وجود خارطة استثمارية واضحة توضح أهم فرص الاستثمار الزراعي في السودان و عدم وجود شراكات إستراتيجية في مجال إنتاج القمح لمواجهة الطلب المتزايد على القمح باعتبار انه الغذاء الرئيسي لمعظم السكان في السودان. The study aimed to identify the elements of agricultural investment in the field of wheat production in Sudan, with the arrival of the results and recommendations that contribute to the promotion of investment in the field of wheat production and shed some light on the position of partnerships in the field of wheat production. The study assumed the availability of the agricultural investment components in wheat production but did not exploit the best exploitation and the lack of strategic partnerships in the field of wheat production to meet the growing demand for wheat. The study adopted the analytical descriptive method that describes and interprets the status quo and thus reaches conclusions and recommendations that contribute to solving the study problem. The study concluded that the absence of an investment map shows the most important opportunities for agricultural investment in Sudan and the lack of strategic partnerships in the field of wheat production to meet the increasing demand for wheat as the main food for most of the population in Sudan.
Components of agricultural investment in wheat in Sudan during the period 1994-2022
Keywords: الاستثمار الزراعي; إنتاج القمح; شراكات إستراتيجية; الغذاء الرئيسي; agricultural investment -; wheat production; - strategic partnerships; main food